2012
DOI: 10.1177/014556131209100316
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Need for Audiologic Evaluation in Patients with Behçet Disease?

Abstract: Behçet disease is known to be a multisystem condition. We conducted a study to determine the prevalence of hearing loss in patients with Behçet disease and to identify any associations between audiologic findings and other clinical manifestations and treatment. Our study group was made up of 41 adults with Behçet disease and 41 healthy sex-and age-matched controls. All patients and controls underwent a complete clinical otolaryngologic examination, which included pure-tone audiometry, acoustic impedance testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Patients with Churg-Strauss syndrome present with allergic rhinitis and nasal polyposis (9,10). Behçet disease is an autoimmune vasculitis that involves the central nervous system and also causes mucosal ulcerations, uveitis, and sensorineural hearing loss in the head and neck (11)(12)(13).…”
Section: Etiology Autoimmune Gdsmentioning
confidence: 99%
“…Patients with Churg-Strauss syndrome present with allergic rhinitis and nasal polyposis (9,10). Behçet disease is an autoimmune vasculitis that involves the central nervous system and also causes mucosal ulcerations, uveitis, and sensorineural hearing loss in the head and neck (11)(12)(13).…”
Section: Etiology Autoimmune Gdsmentioning
confidence: 99%
“…Even Cinar et al [6] more recently revealed that the prevaÌence of SNHL was signiflcantly highel in the BehEet patients than in the controls. The duration of Behqet's disease had no signiflcant impact on whether patients did or did not experience hearing loss.…”
mentioning
confidence: 91%